Motivations, Behaviors and Expectancies of Sexting: The Role of Defensive Strategies and Social Media Addiction in a Sample of Adolescents - Ragona, Alessandra; Mesce, Martina; Cimino, Silvia; Cerniglia, Luca (International journal of environmental research and public health, 2023)
Adolescents and young adults engage in sexting behaviors. Research has mainly emphasized the relationship between motivations and sexting behaviors, with little attention paid to sexting expectations and the potential role of coping strategies. This study aims to explore the measure of emotional–behavioral functioning with the Youth/Adult Self Report (based on the subject’s age), the use of defensive strategies measured with the Response Evaluation Measure (REM-71), social media addiction with the Bergen Social Media Addiction Scale (BSMAS) and all dimensions of sexting: motivations, behavior and expectations measured with the Sexting Motivation Questionnaire (SMQ), Sexting Behavior Questionnaire (SBQ) and Sexpectancies Questionnaire (SQ), respectively. N = 209 adolescents and young adults were recruited from high schools and universities in Rome to complete the self-report questionnaires. Results show that males tend to have higher expectations of sexting than females. We also found that expectations play a role in determining sexting behaviors and motivations. Our hypotheses on social media addiction and sexting were confirmed, while the relationship between the defensive strategies and sexting was not significant as expected. Further studies on this topic are desirable in the future.